Are mechanical and electromechanical methods accurately interchangeable for measuring plasma prothrombin time and activated partial thromboplastin time? A comparative analysis study and potential implication to cardiovascular disease - Pranata, Fransiska Jaya; Notopuro, Paulus Budiono; Hajat, Arifoel (Heart Science Journal, 2025)
INTRODUCTION: The DT100 offers both optical and mechanical modes, with its mechanical mode showing better homogenization than the STAGO, but comparative study is limited. OBJECTIVES: The study aimed to evaluate the diagnostic accuracy of plasma Prothrombin Time (PT) and Activated Partial Thromboplastin Time (APTT) measurements using the DT100 and STAGO instruments. METHODS: Designated as a cross-sectional study, this study was conducted at RSUD Dr. Soetomo from October 2022 to January 2023. Venous blood samples with plasma citrate anticoagulant 0.109 M 3.2% were consecutively collected from hospitalized patients, and all samples underwent testing using both the DT100 in mechanical mode (DT100, TCoag Ireland Limited, Ireland) and the STAGO employing an electromechanical method (Compact Max3, STAGO, France). Statistical analysis included comparison using Paired t-test, Pearson correlation, and Bland-Altman analysis to assess agreement between the results obtained from the two instruments. RESULTS: The study included 51 patients. PT levels were significantly lower with the DT100 compared to STAGO (MD: -2.0; 95%CI: (-2.30) – (-1.3); p<0.0001), and showed a strong positive correlation between methods (r:0.9535; p<0.0001). However, Bland-Altman analysis for PT showed a bias of 1.84, with limits of agreement (3.30-0.37), indicating systematic differences and variability. APTT levels were significantly higher with DT100 compared to STAGO (MD:3.60; 95%CI: 2.13–5.07; p<0.0001), with a moderate positive correlation (r:0.6690; p<0.0001). For APTT, bias of Bland-Altman analysis was -3.60, with limits ((-9.84) – (2.64)), suggesting significant discrepancies and variability between methods. CONCLUSION: The study found significant variability in PT and APTT measurements between the DT100 and STAGO methods.